SOBM - Server Occupancy Based Migration by Optimizing Link and Storage Capacity in Check Points - N. Unnithan, Sreeleja; Bhavani, S (International Journal of Engineering and Technology, 2018)
Checkpoint (CP) routing requires a procedure for heavy load and dynamic routing packets over a cluster network, by monitoring network load.Â High traffic CP network does intense transactions by multiple applications and shares the information among the nodes in the network and delivers the same to the server. The Proposed work assigns time slots and each slot checks the path to send or migrate the data to manage the load and data accumulation between servers and if there arises any data loss it recovers from the previous node buffers.Â Data rate and delay is checked by each link and adjust the data flow to various servers. Based on time, network state, incoming packet rates, server load, link-based migration is applied. It increases network packets receiving rates, and minimizes the delay in checkpoints. Â Â